1997
DOI: 10.1126/science.278.5345.1907
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Catalytic Domains of Adenylyl Cyclase in a Complex with G ·GTPγS

Abstract: The crystal structure of a soluble, catalytically active form of adenylyl cyclase in a complex with its stimulatory heterotrimeric G protein alpha subunit (Gsalpha) and forskolin was determined to a resolution of 2.3 angstroms. When P-site inhibitors were soaked into native crystals of the complex, the active site of adenylyl cyclase was located and structural elements important for substrate recognition and catalysis were identified. On the basis of these and other structures, a molecular mechanism is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
974
1
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(1,010 citation statements)
references
References 46 publications
29
974
1
5
Order By: Relevance
“…Although sACs have unique regulatory properties, the overall structure and active site of CyaC (Fig. 1a,b) closely resemble the known structure of mammalian tmAC 12 . The only difference is that CyaC is a symmetrical homodimer of a single catalytic domain with two complete active sites, whereas tmACs are pseudo symmetrical heterodimers of structurally similar catalytic domains (C 1 and C 2 ), resulting in one active site and one degenerate pseudo active site.…”
Section: αβ-Me-atp Binds To An Open Enzyme Statementioning
confidence: 70%
See 1 more Smart Citation
“…Although sACs have unique regulatory properties, the overall structure and active site of CyaC (Fig. 1a,b) closely resemble the known structure of mammalian tmAC 12 . The only difference is that CyaC is a symmetrical homodimer of a single catalytic domain with two complete active sites, whereas tmACs are pseudo symmetrical heterodimers of structurally similar catalytic domains (C 1 and C 2 ), resulting in one active site and one degenerate pseudo active site.…”
Section: αβ-Me-atp Binds To An Open Enzyme Statementioning
confidence: 70%
“…Previous work has revealed the overall structure of tmAC enzymes and suggested a twometal ion mechanism for catalysis 12,13 . Despite their different regulation, mammalian sAC and tmACs are grouped into the nucleotidyl cyclase class III based on sequence similarities within their catalytic domains 14 .…”
mentioning
confidence: 99%
“…Here, Fsk stabilizes the interaction of the C1 and C2 subunit of adenylyl cyclase, thereby enhancing the activity of this enzyme [40]. In the crystal structures of either the C2 homodimer [41] or the C1-C2 heterodimer complexes with the stimulatory a subunit of a trimeric G protein (Gsa) [42], Fsk binds to a composite pocket in the rim of the dimer interface. This binding site is strongly hydrophobic and buries 90% of the solvent-accessible surface of Fsk.…”
Section: Forskolinmentioning
confidence: 99%
“…Although AC has two ATP binding domains, it has been shown that these domains are inactive separately and require dimerization for AC activity. 51 This fact allows us to introduce a simplification and consider a model of AC with one catalytic centre that describes the activity of the two domains. The multiple G-protein subunits (15a, 5b and 13g) together with the nine membrane bound AC isoforms raise the issue of selectivity between the interacting partners.…”
Section: Resultsmentioning
confidence: 99%